2021
DOI: 10.34133/2021/9816485
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosed Polyhedrin-Cytokine Cocrystal Nanoparticles Provide Sustained Secretion of Bioactive Cytokines from Macrophages

Abstract: Many cells possess the ability to engulf and incorporate particles by phagocytosis. This active process is characteristic of microorganisms as well as higher order species. In mammals, monocytes, macrophages, and microglia are among the so-called professional phagocytes. In addition, cells such as fibroblast and chondrocytes are classified as nonprofessional phagocytes. Professional phagocytes play important roles in both the innate and adaptive immune responses, wound healing, and tissue homeostasis. Conseque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…There was a direct relationship between the number of PODS and the amount of accumulated IL-2 detected by the ELISA assay. As had been observed in our previous study 5 , where human IL-6 release was measured from phagocytosed PODS, ingestion by macrophages significantly reduces the amount of free cargo protein accumulating in the media. In the absence of macrophages, (measured only on day 6) the amount of IL-2 that accumulated was about 10-fold higher.…”
Section: In Vitro Il-2 Levelssupporting
confidence: 79%
See 3 more Smart Citations
“…There was a direct relationship between the number of PODS and the amount of accumulated IL-2 detected by the ELISA assay. As had been observed in our previous study 5 , where human IL-6 release was measured from phagocytosed PODS, ingestion by macrophages significantly reduces the amount of free cargo protein accumulating in the media. In the absence of macrophages, (measured only on day 6) the amount of IL-2 that accumulated was about 10-fold higher.…”
Section: In Vitro Il-2 Levelssupporting
confidence: 79%
“…As may be predicted from their physical characteristics 12 (size, shape, surface charge and elasticity), we previously reported 5 that PODS are efficiently taken up by phagocytic cells in-vitro. We also demonstrated that, following phagocytic uptake, the PODS cargo proteins are sustainably secreted in a bioactive form that is able to modulate the phenotype of adjacent heterogenous cells.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…They showed that PODS particles are very efficiently phagocytosed and that cargo cytokines avoid or resist the harsh conditions of phagolysosomes and enable secretion by macrophages. These results suggest the potential utility of PODS in Trojan horse drug delivery strategies for the treatment of cancer [ 206 ].…”
Section: Unconventional Nanocarriersmentioning
confidence: 99%